Modern Features of Digitalization Implementation in Small Business in the Trade Sector - Popov Oleksandr S.; Makarov Serhii A. (Problemi Ekonomiki)
The article explores the impact of digitalization on the competitiveness of small businesses in the trade sector. The article discusses the main opportunities and challenges arising in the process of implementing digital technologies; analyzes how they contribute to the growth of enterprises, increase productivity, and expand sales markets. Key trends in digital transformation are identified, including the automation of business processes, the personalization of customer experience, and the implementation of cloud technologies. An analysis of literary sources suggests that digitalization is a key factor in the successful development of small businesses, but it requires a comprehensive approach. The implementation of modern technologies contributes to increasing the efficiency of business processes, reducing costs, and strengthening competitive positions in the market. It has been determined that the important elements of successful digital transformation are the integration of digital platforms, the use of analytical tools for managerial decision-making, and the enhancement of digital literacy among entrepreneurs. Special attention is given to the barriers of digital transformation, including financial constraints, a lack of digital literacy, the complexity of implementing technology, and increasing competition. The issue of small businesses adapting to rapid changes in the digital environment has been studied, as well as the need for a strategic approach to digital transformation. Recommendations for overcoming these challenges are provided, particularly through staff training, engaging accessible digital tools, and integrating omnichannel strategies. The question of government support for the digitalization of small businesses has been specifically addressed, including financial incentives, educational programs, and the development of digital infrastructure. Directions for further research are proposed, including the development of an integrated methodology for assessing the level of digital maturity of enterprises. The study of the digital competitiveness of small businesses requires further empirical analysis, which will enable the evaluation of the efficiency of various approaches and the identification of optimal strategies for the digital adaptation of enterprises in the trade sector.